OPTIMASI PARAMETER PROSES 3D PRINTING TERHADAP KELENGKUNGAN SOFT PNEUMATIC GRIPPER DENGAN MENGGUNAKAN FILAMENT EFLEX - Hasdiansah, Hasdiansah; Viniolita , Thala Viniolita; Pristiansyah , Pristiansyah; Herianto , Herianto (Jurnal Rekayasa Mesin, 2024)
The emergence of 3D Printing technology has influenced several industries.3D Printing quickly produced mechanical components and prototype products with low production volumes. This research uses Cartesian DIY (Do It Yourself) 3D Printer and Eflex filament as material. This study aims to obtain the optimal process parameters set on the slicing software with the soft actuator angular response by giving two variations of 0.4 MPa and 0.6 MPa compressed air. Process parameters used in this study are flowrate, nozzle temperature, printing speed, and fan speed. This study aims to obtain the 3D printing process parameters using Fused Deposition Modeling (FDM) technology in producing soft actuators with the most optimal curvature angle using the Taguchi L9OA method. Measurement of soft actuator curvature angle using Fiji Image software. Based on the test results and the calculation of Taguchi analysis on the soft actuator curvature angle, the process parameter settings obtained in the slicing software for a pressure of 0.4 MPa are a flowrate of 105%, a nozzle temperature of 225 ºC, a printing speed of 30 mm/s, and a fan speed of 50%.  Testing 0.6 MPa pressure is flowrate 105%, nozzle temperature 225 ºC, fan speed 50%, and printing speed 30 mm/s.